Effects of Pilot Plant‐Scale Ultrasound on Palm Oil Separation and Oil Quality. (5th May 2013) - Juliano, P.; Swiergon, P.; Lee, K. H.; Gee, P. T.; Clarke, P. T.; Augustin, M. A.
Abstract: The effects of ultrasonic standing waves on palm oil separation of ex‐screw press feed from the mesocarp of the palm oil fruit, oil recovery and oil quality were determined. The ex‐screw press feed at 85 °C was pumped simultaneously into two identical vessels. One vessel was the control (non‐ultrasound) and the other vessel (ultrasound) was fitted with two 400 kHz transducer plates operating at 13.4 kJ/kg, which were placed in direct contact with the feed. Oiling‐off by gravity settling occurred at faster rates after sonication. The total recoverable oil after 30 min gravity settling and upon centrifuging the underflow sludge (remaining colloidal fraction) at 1000× g was higher after sonication. Total recoverable oil was 30.7 ± 2.9 % and 43.5 ± 8.6 % (w/w original feed basis) for the non‐sonicated and sonicated samples respectively. Sonication reduced the oil content of the sludge ex‐centrifuge, demonstrating that higher recovery of palm oil was obtained with ultrasound application. Sonication did not affect the DOBI (deterioration of bleachability index) value, and vitamin E and free fatty acid contents of the separated oil. High‐frequency ultrasound enhances the separation rate of palm oil and increases oil recovery without compromising oil quality.